Linking nutrition education and farm production diversification to fruit and vegetable consumption in Zimbabwe - Conrad Murendo; Dowsen Sango; Claudious Hakuna (Cogent Food & Agriculture, 2023)
AbstractThe main aim of the research was to analyze whether nutrition education and farm production diversification improved household dietary diversity as well as fruit and vegetable consumption among rural households in Zimbabwe. A cross-sectional survey using systematic random sampling was conducted in eight rural districts covering 1417 households. Poisson, Instrumental Variables Poisson, and Instrumental Variables probit regressions were used for analysis. Nutrition education and farm production diversity were associated with 53% and 2% increase in household dietary diversity, respectively. Nutrition education shows a significant and positive association with both fruits and vegetables intake. Nutrition education was associated with a 50% and 18% likelihood of consuming fruits and vegetables, respectively. Farm production diversification was associated with fruit consumption among rural households. Using alternative model specifications, we note that nutrition education was associated with an increase in the frequency of consuming vegetables. Farm production diversification and income were positively correlated with the frequency of fruit intake. Therefore, government, private sector, and development agencies need to promote nutrition education programs that emphasize production and consumption of fruits and vegetables. Second, interventions that promote crop and livestock diversification, including household cultivation of nutrient-rich fruits and vegetables, need to be upscaled.